LE BRETON, D. (2021). Antropologia del Corpo. Milano: Meltemi Editore - Lopes, Eugénio (Daimon Revista Internacional de Filosofia, 2024)
Reseña de: LE BRETON, D. (2021). Antropologia del Corpo. Milano: Meltemi Editore, 326 pp.